Pemakaian Bahasa Inggris Formal dan Informal oleh Pengusaha Ukir Jepara - Wiwiek Sundari (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This article was written based on the results of research conducted in Jepara entitled Use of Formal and Informal English Basaha by Carving Entrepreneurs in Jepara. The purpose of this study was to describe the use of formal English (written) and informal (verbal) by carving entrepreneurs in Jepara. Data collection was carried out in three ways, namely secondary data, questionnaires, and interviews. Questionnaires were given to respondents consisting of large entrepreneurs, medium-sized entrepreneurs, and small-scale entrepreneurs. The results of the study illustrate that the level of use of formal English is mostly done by large entrepreneurs. The use of informal English from the three groups of different intensity categories is caused by contact with different buyers.